Determination of factors affecting safety practices in Malaysian radiation facilities - Kasim, Hazmimi; Hassan, Che Rosmani Che; Hamid, Mahar Diana; Emami, Sina Davazdah; Danaee, Mahmoud (Elsevier, 2018)
A substantial amount of research has delved into the nature of safety climate, and subsequently its importance as a leading indicator of safety performance. However, they have mostly been conducted in Western countries via high risk operations. Therefore, this study is focused on the exploratory factors of safety culture practice in the industrial context of Malaysian radiation facilities, specifically by determining the influencing factors, their dependency and significant difference in mean level. This is attempted by adopting and adapting the six-factor Malaysian Safety Tool Kit (MSTK) and the components of safety culture practice as suggested by International Atomic Energy Agency (IAEA) safety series as the Malaysian nuclear and radiation safety tool kit (MRSTK). The exploratory factor analysis representing the MSTK model is therefore partially replicated and applied in the Malaysian nuclear and radiation sector. An alternative nine-factor model has been developed, which consisted of 32 items encompassing these elements accordingly: questioning attitude, communicative information, work environment, management commitment, communication, safety priority, personal view, involvement and prudent approach. The resulting outcomes have displayed statistically significant mean difference among these factors and consequently remained consistent with common safety climate themes. Nevertheless, they have also demonstrated the need to factor in individual response and organization cultural factors in the development of safety climate models intended for usage in Malaysian radiation sector. Furthermore, these findings have also revealed implications regarding the transferability of safety climate models and the type of safety interventions in implementing Occupational Health and Safety (OHS) management strategies more efficiently.